Development and Validation of Module in Fluid Physics - Charlie Torres Anselmo (East Asian Journal of Multidisciplinary Research, 2023)
The researcher opts for the study entitled Development and Evaluation of Module in Fluid Mechanics. The purpose of this study is to develop instructional module in Fluid Mechanics. Specificallyi.it aimed to evaluate the module in terms of content, design and features, organization and presentation, clarity, assessment, style or Creativity, and illustration. This study made use of the descriptive comparative research design. It described the modules and compared the assessment of respondents in terms of Learning outcomes/objectives, Structure and Layout, Self-assessment Questions and Activities, Response to Self-Assessment Questions, The Text itself, Learning Content, General Instructional, and Vocabulary and it compared the ratings given by teachers and students. The instrument used in the study was a questionnaire developed by the researcher and validated by the experts using five (5) point rating scale for the eight (8) aspects of modules The respondents of the study were the Nine (9) Physics faculty of Isabela state University and the thirteen (13) Science major students chosen through purposive sampling. The data were tabulated and illustrated to arrive significance finding thru mean, standard deviation and t-test. The study revealed that the developed learning modules in Fluid Mechanics are acceptable learning material for teachers and students of Isabela State University. In regard to the evaluation of the developed modules, students desire a better quality of module than the teachers particularly in terms of layout and structure. Meanwhile, teachers have better appreciation for the modules’ learning objectives than the students due to teaching experience and maturity.